Leveraging blockchain and artificial intelligence for enhanced copyright enforcement in South Africa - Mugauri, Joseph (Department of Commercial Law, 2025)
Leveraging Blockchain and Artificial Intelligence for Enhanced Copyright Enforcement in South Africa The Fourth Industrial Revolution has significantly impacted copyright enforcement, particularly in South Africa, where technological advancements have bolstered and challenged existing frameworks. This dissertation explores the integration of blockchain and artificial intelligence (AI) to enhance copyright enforcement mechanisms in the digital realm. Current enforcement methods face several challenges, including lengthy legal proceedings, slow legislative updates, circumvention techniques, accessibility concerns, non-compliance, and algorithmic bias. These issues necessitate innovative solutions to protect intellectual property rights effectively. With its decentralised and immutable nature, blockchain technology offers promising solutions for transparent and efficient copyright enforcement. Concurrently, AI technologies such as machine learning, deep learning, and adaptive algorithms can enhance the detection and prevention of copyright infringements, including brute force attacks, malware, phishing, and illegal streaming. This research delves into the potential of AI and blockchain for detecting infringing content, blockchain-based arbitration platforms for resolving disputes, and adaptive watermarking algorithms to trace the unauthorised use of digital content. The benefits of these technologies include increased efficiency, improved accuracy, transparency, and traceability. However, implementing these technologies poses challenges such as regulatory compliance, privacy concerns, ethical considerations, and associated costs. It recommends policy updates, ethical guidelines, and collaborative efforts to ensure blockchain and AI's responsible and effective use in copyright enforcement. By leveraging these technologies, South Africa can strengthen its copyright framework, fostering creativity and innovation while safeguarding intellectual property rights in the digital age.